Industrial Halal hunted-game and feral animals' meat production. (November 2021) - Farouk, MustafaM.; Strydom, Phillip; Dean, Rachael; Vather, Nadia; Gcabo, Mike; Amir, Mohammad
Abstract: Hunted wild game meat (HGM) is growing in popularity and attracting a premium among consumers. This has led to the emergence of supply chains for industrially produced HGM in many countries. With the growing demand for Halal meat and the disposable income of its consumers around the globe, meat and game industries in countries rich in wild game and feral animals would be encouraged to consider supplying Halal hunted game meat (HHGM) to Halal consumers around the world. Meeting the Halal requirements for industrial HHGM is easy given the already existing supply chains for HGM in many producing countries. What is needed by the Game and Meat Industries in these countries to comply with the Halal requirements in terms of the hunted animal and the hunter, the hunt location, modes and methods, the handling and processing of hunted carcases and the hunted animal welfare and sustainability in the industrial production of HHGM, is the subject of this review.